Nrl-Cre transgenic mouse mediates loxP recombination in developing rod photoreceptors - Brightman, Diana S. (Genesis, 2016)
The developing mouse retina is a tractable model for studying neurogenesis and differentiation. Although transgenic Cre mouse lines exist to mediate conditional genetic manipulations in developing mouse retinas, none of them act specifically in early developing rods. For conditional genetic manipulations of developing retinas, we created a Nrl-Cre mouse line in which the Nrl promoter drives expression of Cre in rod precursors. Our results show that Nrl-Cre expression is specific to the retina where it drives rod-specific recombination with a temporal pattern similar to endogenous Nrl expression during retinal development. This Nrl-Cre transgene does not negatively impact retinal structure and function. Taken together, our data suggest that the Nrl-Cre mouse line is a valuable tool to drive Cre-mediated recombination specifically in developing rods.